Back to BAC: Insights into Boronate Affinity Chromatography Interaction Mechanisms. Issue 3 (3rd July 2018) - Espina-Benitez, Maria Betzabeth; Randon, Jérôme; Demesmay, Claire; Dugas, Vincent
Abstract : Boronate affinity chromatography (BAC) is commonly used in sample preparation techniques for its specific selectivity for cis-diol-containing compounds. Various chromatographic materials based on phenyl-boronic acid (PBA) functionalization have been designed. This review aims to present the versatility of the underlying BAC mechanisms. The PBA moiety presents secondary/complementary/interfering interactions, i.e., hydrophobic, electrostatic and/or hydrogen-bonding interactions. The comprehensive understandings of these mechanisms are very helpful to manipulate separation selectivity, which is a key feature in biomolecular sample treatment. Each BAC interaction is reviewed and illustrated by specific examples. Special attention is given to the underlying role of PBA supports for sugars, glycans and glycoconjugates recognition.